2016
DOI: 10.1007/s40272-016-0168-2
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Oncology: Managing Pain at the End of Life

Abstract: Pain is a common and highly distressing symptom in pediatric patients with advanced malignancies. Prompt recognition, assessment, and treatment of pain are necessary, especially at the end of life. Opioid medications remain the mainstay of treatment of malignant pain in children at the end of life and the amount of opioids required for adequate pain control in patients is highly variable. Nonpharmacological approaches including behavioral and physical approaches in addition to non-opioid pain medications shoul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
23
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 102 publications
0
23
0
Order By: Relevance
“…While NP is well characterized in adults with cancer [3][4][5][6][7][8][9][10][11][12][13][14][15], it is less well described in pediatric oncology [16][17][18][19][20][21][22]. In the setting of pain in pediatric oncology patients, NP can be caused by a variety of types of somatosensory system injuries including chemotherapyrelated NP [19,23], tumor-related NP [24][25][26], post-surgical NP [27,28], and the complex circumstances of NP at the end-of-life [29]. The most commonly incriminated chemotherapy agent related to neurotoxicity and NP in children is vincristine.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While NP is well characterized in adults with cancer [3][4][5][6][7][8][9][10][11][12][13][14][15], it is less well described in pediatric oncology [16][17][18][19][20][21][22]. In the setting of pain in pediatric oncology patients, NP can be caused by a variety of types of somatosensory system injuries including chemotherapyrelated NP [19,23], tumor-related NP [24][25][26], post-surgical NP [27,28], and the complex circumstances of NP at the end-of-life [29]. The most commonly incriminated chemotherapy agent related to neurotoxicity and NP in children is vincristine.…”
Section: Introductionmentioning
confidence: 99%
“…Post-surgical NP related to mechanical nerve trauma in pediatric oncology has a prevalence of 81.6% after surgery for osteosarcoma with either postamputation phantom limb pain (PLP) or as NP after limb sparing surgery [27]. NP at the end of life is often related to complex circumstances and may include mixed nociceptive and neuropathic mechanisms [29].…”
Section: Introductionmentioning
confidence: 99%
“…Pain may result not only from primary cancer and/or metastasis but also from treatment procedures and side effects (Bukola & Paula, 2017;Duffy et al, 2019;Twycross et al, 2015). In other cases, pain is associated with endstage or terminal disease (Snaman et al, 2016;Ye et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8][9] Interdisciplinary teams are best equipped to provide such treatment because they can complement medical pain management by addressing the complex issues underlying pain. 10 Although nonopioid analgesics and nonpharmacologic approaches are used to manage cancer pain, opioids remain a mainstay of treatment. 10,11 Indeed, a retrospective review conducted at St. Jude Children's Research Hospital found that 23.6% of AYAs with cancer are prescribed opioids.…”
Section: Introductionmentioning
confidence: 99%
“…10 Although nonopioid analgesics and nonpharmacologic approaches are used to manage cancer pain, opioids remain a mainstay of treatment. 10,11 Indeed, a retrospective review conducted at St. Jude Children's Research Hospital found that 23.6% of AYAs with cancer are prescribed opioids. 12 Although most patients used opioid medications as prescribed, 11.7% exhibited aberrant opioid-associated behavior (AOB).…”
Section: Introductionmentioning
confidence: 99%